Integrating Multicultural Islamic Education With a Love-Based Curriculum and Deep Learning: A Holistic Framework for Enhancing Student Character and Empathy in Indonesian Madrasahs - Saepudin Mashuri; Mufiqur Rahman (Jurnal Studi Pendidikan Agama Islam, 2026)
This study aims to develop and examine a holistic framework integrating multicultural Islamic education, a love-based curriculum, and deep learning to enhance students’ character and empathy in Indonesian madrasahs. Using a mixed-methods sequential explanatory design, quantitative data were collected through pre-test and post-test surveys, while qualitative data were obtained via classroom observations and in-depth interviews. The findings reveal a significant improvement in students’ empathy and character, supported by statistical analysis (p < 0.001). The integration of compassionate values within a multicultural and reflective learning environment fosters meaningful learning experiences and strengthens social awareness. Furthermore, the study identifies a novel integrative model that combines cognitive, affective, and social dimensions in a unified pedagogical approach. This model contributes both theoretically, by enriching the discourse on Islamic education, and practically, by offering an adaptable framework for curriculum development in madrasahs. The study highlights the urgency of transforming traditional instructional approaches into more humanistic, inclusive, and contextually relevant practices.